Reforming Human Resource Management in Islamic Education: Strategic Approaches to Enhancing Teacher Quality at MAN 1 Pesawaran - Ananda Junia Ningsih; Nor Rochmatul Wachidah (WISE Pendidikan Indonesia, 2025)
This study aims to analyze the implementation of Human Resource Management (HRM) in enhancing the quality of educators at Madrasah Aliyah Negeri 1 Pesawaran, Lampung. HRM plays a strategic role in maximizing organizational performance through the effective management of development, integration, maintenance, and discipline of educators. The research employs a qualitative descriptive approach with data collection techniques including interviews, observations, and documentation involving the headmaster, vice principal for curriculum, and teachers. The findings indicate that (1) educator development is systematically carried out through routine online and offline training; (2) the integration process fosters structured collaboration with both internal and external parties to enhance the quality of learning; (3) human resource maintenance is based on short- to long-term strategic plans; and (4) discipline is effectively implemented, as reflected in the teachers' consistent responsibility and performance. Performance evaluations are conducted periodically and supported by a reward system that encourages professionalism and motivation among educators. Despite budgetary constraints, collaboration with external parties has become a solution to support sustainable professional development. These findings show that effective HRM practices significantly contribute to improving the quality of educators and educational outcomes. This study provides practical insights for other educational institutions in designing adaptive HRM strategies in the global era.